A novel class of fast‐acting antimalarial agents: Substituted 15‐membered azalides. (16th December 2020) - Peric, Mihaela; Pešić, Dijana; Alihodžić, Sulejman; Fajdetić, Andrea; Herreros, Esperanza; Gamo, Francisco Javier; Angulo‐Barturen, Iñigo; Jiménez‐Díaz, María Belén; Ferrer‐Bazaga, Santiago; Martínez, María S.; Gargallo‐Viola, Domingo; Mathis, Amanda; et al.
Abstract : Background and Purpose: Efficacy of current antimalarial treatments is declining as a result of increasing antimalarial drug resistance, so new and potent antimalarial drugs are urgently needed. Azithromycin, an azalide antibiotic, was found useful in malaria therapy, but its efficacy in humans is low. Experimental Approach: Four compounds belonging to structurally different azalide classes were tested and their activities compared to azithromycin and chloroquine. in vitro evaluation included testing against sensitive and resistant Plasmodium falciparum, cytotoxicity against HepG2 cells, accumulation and retention in human erythrocytes, antibacterial activity, and mode of action studies (delayed death phenotype and haem polymerization). in vivo assessment enabled determination of pharmacokinetic profiles in mice, rats, dogs, and monkeys and in vivo efficacy in a humanized mouse model. Key Results: Novel fast‐acting azalides were highly active in vitro against P. falciparum strains exhibiting various resistance patterns, including chloroquine‐resistant strains. Excellent antimalarial activity was confirmed in a P. falciparum murine model by strong inhibition of haemozoin‐containing trophozoites and quick clearance of parasites from the blood. Pharmacokinetic analysis revealed that compounds are metabolically stable and have moderate oral bioavailability, long half‐lives, low clearance, and substantial exposures, with blood cells as the preferred compartment, especially infected erythrocytes. Fast anti‐plasmodial action is achieved by the high accumulation into infected erythrocytes and interference with parasite haem polymerization, a mode of action different from slow‐acting azithromycin. Conclusion and Implications: The hybrid derivatives described here represent excellent antimalarial drug candidates with the potential for clinical use in malaria therapy.